AGRICULTURAL COST MANAGEMENT THROUGH A DYNAMIC TOOL. STUDY CASE: A COMPANY SITUATED ON THE SOUTHWEST OF BUENOS AIRES (Costos y Gestión, 2021)
This article has been written based on the Specialization in Costs and Business Management’s final instance. The scarcity of cost management tools with an economic focus on agricultural small and medium-sized enterprises also with the detected needs of a producer of Buenos Aires, triggered this study case. Based on the needs of the mentioned producer and considering the cost theory supported by the Argentine Institute of University Professors of Costs (IAPUCo), a cost management tool was designed. It allows answering certain questions that help the decision-making process of the company. The designed tool is dynamic and flexible with the aim of being able to be used by other companies, adapting it to the particular requirements of each one.
Keywords: Agricultural Small and medium-Sized Enterprises; Costs, Business Management: Decision Making Process; TGC; Direct Costing